(untitled) (Eurasian Scientific Herald, 2023)
the article discusses the advantages and disadvantages of the institution of selfemployment under the legislation of the Republic of Uzbekistan, identifies the advantages of self-employment. Five reasons for motivating self-employment are indicated and analyzed. The experience of legal regulation of the order of self-employment in the legal order of foreign countries is considered.